A GSM-Free IOT Architecture for Smart Vehicle Anti-Theft and Multi-Mode Safety Monitoring Using ESP32 with Telegram Bot Integration (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Road traffic fatalities in developing economies are significantly attributed to vehicle theft, alcohol-impaired driving, and inadequate emergency response following accidents. Despite this critical need, cost-effective embedded solutions that simultaneously address these three safety challenges remain inaccessible to typical vehicle owners. This research introduces an integrated smart vehicle monitoring platform that operates without SIM card dependency, utilizing the ESP32-WROOM-32 microcontroller as its foundation. The system executes six concurrent operational functions within a unified architecture: (i) GPS-based anti-theft notifications transmitted as interactive Google Maps links via Telegram Bot API through Wi-Fi connectivity, (ii) breath alcohol sensing through MQ-3 sensor integration with automated ignition prevention mechanisms, (iii) collision and vehicle rollover identification using MPU6050 six-axis inertial measurement technology enhanced with rolling-average algorithms for false alarm mitigation, (iv) intelligent headlight control based on ambient light conditions through LDR voltage divider implementation, (v) proximity alert functionality utilizing HC-SR04 ultrasonic sensing with progressive warning zones, and (vi) browser-accessible Pilot Console dashboard hosted locally on ESP32 flash storage, enabling network-wide access without specialized applications. Performance validation through controlled laboratory conditions and real-world field testing yielded a mean Telegram notification delay of 3.1 seconds, comprehensive detection reliability of 98.0% across 60 experimental trials, GPS positioning accuracy of 3.2 meters CEP, and complete alcohol detection precision across 10 validation tests. The complete hardware implementation costs Rs. 1,185 with no ongoing communication expenses. The design deliberately excludes LCD displays, SIM cards, and GSM components throughout the entire system architecture.